(untitled) (Global Journal of Human-Social Science, 2024)
This reflection aims to be a simple contribution in the most significant way possible to the debate on the ways and assumptions to think about educational progress in Mozambique It is therefore a reflection that starting from an ideological discourse and being based on the political perspective flows into axiological reflection that is on the values that according to Castiano and Ngoenha are configured as being maximum exponents of education in the Mozambican conjuncture The idea of educational progress from a generic point of view is also scrutinized by several Mozambican thinkers However the reading and interpretation given by the thought of the Mozambican philosophers Castiano and Ngoenha finds its possibility of application in the current Mozambican scenario characterized to a large extent by instability and educational crisis Thus based on the paths and assumptions of ideology politics and axiology approaches with a very significant echo in Mozambican education a digression will be made with the purpose of demonstrating that Mozambique with discernment and wisdom can make use of the tripod or the triple ideology politics and axiology to overcome the current situation of educational crisis to bring about substantial changes to build and maintain an education system capable of strengthening educational institutions to moralize formal education and to ensure robust and transparent education